Loss of Stability of Thin-Walled Conical Shells with Circumferential Ring Loaded by Axial Force - Yilmaz, Haluk (Univerzita Pardubice, 2019)
This dissertation is devoted to the effects of the circumferential ring on the loss of stability of the conical shells loaded by an axial force. The truncated conical shell with different shell thicknesses and base angles at the lower edge are investigated in this thesis. The main aim is a proposal a new method to calculation of load carrying capacity of the conical shell structures with a base angle less than 25° loaded by axial force. The proposed method is applicable for different radial stiffness of the circumferential ring. Two dimensionless similarity parameters are used in this method. Numerical models are created in COSMOS/M package program. The numerical analyses were performed for different angles, shell thickness and radial stiffness of circumferential ring. Empirical relationships are established based on the results of the numerical analysis.
Ztráta stability tenkostěnných kuželových skořepin s obvodovým prstencem zatížených osovou
Keywords: kuželová skořepina; obvodový prstenec; únosnost; osové zatížení; MKP; conical shell; circumferential ring; load carrying capacity; axial loading; FEM